Sombano Lake Tourist Attraction on Kaledupa Island, Wakatobi Regency - Novri, Novri; Nahdatunnisa, Nahdatunnisa; Syah, Andi Al Mustagfir (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tourism involves individual or group travel to enjoy the beauty of an object or tourist attraction. The rapid development of tourism in Wakatobi Regency has encouraged me to highlight one of the destinations, namely Lake Sombano, which is famous for its natural and well-maintained environmental sustainability. Lake Sombano Tourism is located near Sombano Village, Kaledupa District, Wakatobi Regency, Southeast Sulawesi, which is not far from residential areas. The method used is a qualitative descriptive method by collecting, analyzing primary and secondary data related to the title, literature studies, comparative studies and observations. The circulation pattern that will be used in the area is a linear and radial circulation pattern in the form of a series of spaces, branching, then also spreading from one point to form aesthetics in the area and also for the comfort of road users of visitors. In planning the Lake Sombano Tourism Object, the design principle used is the ecological concept in landscape design that is friendly to the surrounding environment and uses materials in accordance with the ecological concept as the main material, and this is a solution to the design of the Lake Sombno Tourism Object on Keledupa Island, Wakatobi Regenc.